L'union du silence et de la parole dans la dramaturgie de Bernard-Marie Koltès - Starak, Grażyna (Romanica Silesiana)
The game of the said, understated and unsaid is revealed by Grażyna Starak, showing the fundamental differences between the text to be said on the stage, and fragments of replicas crucial for the text to be understood inserted in brackets which the author does not approve of uttering at the time of the performance. Keywords : Koltès; drama; the unsaid; dialogue; unsaid reply lines